Analysis of Stress Management on Nutritional Status and Anxiety Levels among STIKes Hang Tuah Surabaya Students Completing their Final Assignments - Dya Sustrami; A.V. Sri Suhardiningsih; Rizky Dzariyani Laili (Universitas STRADA Indonesia, 2025)
Background: Students who are dealing with their thesis often experience anxious and often neglect proper dietary management, potentially leading to changes in their nutritional their nutritional status. Each student engaged in completing their final assignment was required to possess effective stress reduction skills to maintain a positive mindset and achieve a state of relaxation, thereby facilitating the successful completion of their final assignment. Purpose: This study aims to evaluate the impact of stress reduction towards nutritional status and anxiousness levels among Stikes Hang Tuah Surabaya students who are completing their final project. Methods: This study uses quantitative research, with the research design is pre-experimental in one group. The population is final grade of students in S1 Nursing and D3 Nursing study programs at Stikes Hang Tuah Surabaya. The sample of this study was taken by simple randomization with a total of 108 students from 148 total population. This study used the Hamilton Rating Scale (HRS) for anxiety questionnaire and anthropometric measurements. Data were analyzed using the Wilcoxon test. Results: The findings showed that the application of stress management methods given three times within one month significantly influenced the anxiety level and nutritional status of students. The Wilcoxon test shows that there is an impact of stress reduction on nutritional status and anxiety levels in facing final year projects at Stikes Hang Tuah Surabaya with the results of the pretest-posttest nutritional status p = 0.002 and the results of the pretest-posttest anxiety level p = 0.000 (p <ɑ = 0.05). Conclusion: The findings of this study suggest that the implementation of stress reduction techniques has a significant impact on the nutritional status and anxiety levels of students completing their final assignments. Consequently, it is recommended that students facing culminating academic projects employ these stress reduction strategies during the course of their work.